Analisis Usability pada Aplikasi Mobile JKN (Studi Kasus: Dosen Universitas Hasanuddin) - Ribal, Arjuna; Sampetoding, Eliyah Acantha Manapa; Hasbi, Muhammad; Amir, Supri Bin hj. (STMIK Banjarbaru, 2025)
As part of the national social security program, BPJS Kesehatan plays a crucial role in providing accessible and affordable healthcare services for the community. The Mobile JKN application aims to enhance the efficiency and accessibility of healthcare services. This study aims to analyze and evaluate the user satisfaction level of the Mobile JKN application within the lecturer community at Hasanuddin University using the End-User Computing Satisfaction (EUCS) and the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) methods as its primary approaches. The EUCS method analysis revealed that, overall, Mobile JKN users feel